Cultural Guardianship in Tourism: Indigenous Communities' Quest for Economic Stability and Identity Preservation - Bhaskar Sailesh; Kiran Reddy (Politeknik Negeri Bandung, 2024)
Indigenous tourism is gaining prominence as a means of economic development, cultural preservation, and community empowerment. This review explores the complex dynamics between tourism development and indigenous communities, considering economic, cultural, social, and environmental impacts. Drawing on historical and contemporary contexts, the review highlights the potential benefits of tourism for indigenous peoples, such as income generation and cultural revitalization, alongside challenges including cultural appropriation and environmental degradation. The review aims to deepen understanding and inform more inclusive and sustainable tourism policies and practices by synthesizing existing research and amplifying indigenous perspectives. Key objectives include analyzing impacts, exploring indigenous perspectives, and identifying future research directions. The findings underscore the importance of balancing economic opportunities with cultural preservation and community well-being in indigenous tourism development, calling for collaborative efforts to uphold indigenous rights, foster cultural authenticity, and enhance socio-economic outcomes.